2014
DOI: 10.12966/abc.02.06.2014
|View full text |Cite
|
Sign up to set email alerts
|

Applying Theoretical Models on Human Creativity to Animal Studies

Abstract: -While creativity in humans has been actively studied for some time, it is only recently been a topic of interest in non-human animals. In order to take advantage of what is already known and to avoid redundancy, communication between those who study humans and animals is crucial. There are several models which are actively used in the study of creativity in humans which can be easily applied to animals to assist with the definition, classification, and characterization of behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 95 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Additionally, foraging for insects requires a high degree of visual concentration as well as an awareness of the surrounding environment (Caine, 1996). It has been suggested that the investment of more time in foraging is a behavioral characteristic of conscientious individuals (Kaufman & Kaufman, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, foraging for insects requires a high degree of visual concentration as well as an awareness of the surrounding environment (Caine, 1996). It has been suggested that the investment of more time in foraging is a behavioral characteristic of conscientious individuals (Kaufman & Kaufman, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the investment of more time in foraging is a behavioral characteristic of conscientious individuals (Kaufman & Kaufman, 2014).…”
Section: Behavioral Personality Assessmentmentioning
confidence: 99%
“…'What was once foraging in a physical space for tangible resources became, over evolutionary time, foraging in cognitive space for information related to those resources' [7, p. 4]. In contrast, other researchers note substantial overlap between creative processes in humans and non-human animals and suggest the two fields of research can benefit from cross-pollination of ideas, concepts and methodologies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, it is clear how this may be the case for nonhuman animals. There are many ways that animals can be intentionally innovative, such as engaging in problem solving activity and using tools to get food (e.g., A. Kaufman & Kaufman, 2014, 2015).…”
Section: The Case Of Shadow Creativitymentioning
confidence: 99%